Genotype‐phenotype study in patients with valosin‐containing protein mutations associated with multisystem proteinopathy. Issue 1 (19th December 2017) - Al‐Obeidi, E.; Al‐Tahan, S.; Surampalli, A.; Goyal, N.; Wang, A.K.; Hermann, A.; Omizo, M.; Smith, C.; Mozaffar, T.; Kimonis, V.
Abstract : Mutations in valosin‐containing protein (VCP), an ATPase involved in protein degradation and autophagy, cause VCP disease, a progressive autosomal dominant adult onset multisystem proteinopathy. The goal of this study is to examine if phenotypic differences in this disorder could be explained by the specific gene mutations. We therefore studied 231 individuals (118 males and 113 females) from 36 families carrying 15 different VCP mutations. We analyzed the correlation between the different mutations and prevalence, age of onset and severity of myopathy, Paget's disease of bone (PDB), and frontotemporal dementia (FTD), and other comorbidities. Myopathy, PDB and FTD was present in 90%, 42% and 30% of the patients, respectively, beginning at an average age of 43, 41, and 56 years, respectively. Approximately 9% of patients with VCP mutations had an amyotrophic lateral sclerosis (ALS) phenotype, 4% had been diagnosed with Parkinson's disease (PD), and 2% had been diagnosed with Alzheimer's disease (AD). Large interfamilial and intrafamilial variation made establishing correlations difficult. We did not find a correlation between the mutation type and the incidence of any of the clinical features associated with VCP disease, except for the absence of PDB with the R159C mutation in our cohort and R159C having a later age of onset of myopathy compared with other molecular subtypes. Abstract : Mutations in valosin‐containing protein (VCP) cause inclusion body myopathy, Paget's disease of bone, frontotemporal dementia, amyotropic lateral sclerosis and Parkinson's disease. We studied the largest group of individuals (total 231: 118 males and 113 females) from 36 families carrying 15 different VCP mutations to establish genotype‐phenotype correlations. Large intrafamilial and interfamilial variations made establishing correlations difficult to establish, except for later age of onset with R159C mutations.